2019
DOI: 10.1017/s1466252319000045
|View full text |Cite
|
Sign up to set email alerts
|

Canine vector-borne disease: mapping and the accuracy of forecasting using big data from the veterinary community

Abstract: Diagnosis, treatment, and prevention of vector-borne disease (VBD) in pets is one cornerstone of companion animal practices. Veterinarians are facing new challenges associated with the emergence, reemergence, and rising incidence of VBD, including heartworm disease, Lyme disease, anaplasmosis, and ehrlichiosis. Increases in the observed prevalence of these diseases have been attributed to a multitude of factors, including diagnostic tests with improved sensitivity, expanded annual testing practices, climatolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
3
16
0
2
Order By: Relevance
“…Canine vector-borne diseases (CVBDs) are caused by several pathogens (parasites, bacteria and viruses) transmitted by ectoparasites, namely ticks, fleas, mosquitoes and sand flies [ 1 , 2 , 3 ]. These pathogens represent a threat for human and animal health throughout continents [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Canine vector-borne diseases (CVBDs) are caused by several pathogens (parasites, bacteria and viruses) transmitted by ectoparasites, namely ticks, fleas, mosquitoes and sand flies [ 1 , 2 , 3 ]. These pathogens represent a threat for human and animal health throughout continents [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research identified dogs as excellent sentinels of human cases of tick-borne disease and as a predictor for tick distributions and range expansion [42][43][44][45][46][47][48][49][50]. Initial county detections of H. longicornis were largely traceable to animal shelters grooming tick-infested dogs (Table 2); thus, we propose dogs presenting to animal shelters can also help with future invasive-tick-species surveillance.…”
Section: Discussionmentioning
confidence: 83%
“…These spillover events have occurred even in areas far from urban centers with large populations of domestic animals, such as Bolivia’s Kaa-Iya del Gran Chaco and Noel Kempff Mercado National Parks [ 18 , 20 ]. Domestic dogs and cats can also serve as sentinels to detect the circulation of important pathogens, including some that are of zoonotic concern [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Currently, there is little understanding of the pathogens that pose a risk for wild carnivores in Central America, or whether domestic animals play a role in these risks.…”
Section: Introductionmentioning
confidence: 99%